Implementasi Program Adiwiyata sebagai Sarana Pelestarian Lingkungan Hidup di SMA Se-Kota Sukabumi - Khatulistiwa, Uta Dwi; Basori , Yana Fajar Basori; Amirulloh, M. Rijal (Public Service and Governance Journal, 2026)
This study aims to analyze the implementation of the Adiwiyata Program as a means of environmental conservation at SMA Negeri 3 Sukabumi City. The Adiwiyata Program is a government effort to increase environmental awareness in schools, with a focus on developing schools that care about and have an environmental culture. This study uses a qualitative approach with descriptive methods, involving observation, interviews, and documentation as data collection techniques. The research informants consisted of the Head of the Adiwiyata Program Division of the Sukabumi City Environmental Agency, the Principal of SMA Negeri 3, and students involved in Adiwiyata activities. The results of the study indicate that the implementation of the Adiwiyata Program at SMA Negeri 3 Sukabumi City has been running quite well. In terms of communication, the program is well socialized to all school residents by the Environmental Agency and the school. In terms of resources, the program is supported by competent human resources and adequate infrastructure. The school's commitment and active student participation are also reflected in the disposition dimension. Meanwhile, in the bureaucratic structure dimension, program implementation is supported by a clear division of tasks through the formation of an Adiwiyata team at the school. This program has succeeded in increasing the school community's awareness and concern for environmental conservation.